1993
DOI: 10.1002/bms.1200220102
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the HMG-CoA reductase inhibitors simvastatin, lovastatin, and pravastatin in plasma by gas chromatography/chemical ionization mass spectrometry

Abstract: A general method for the assay of the 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase inhibitors lovastatin, pravastatin, and simvastatin in plasma has been developed and validated. The analytes are isolated from plasma by a solid-phase extraction procedure which separates the lactone and acid forms of the drugs. The lactone is converted to the acid form, which is subsequently derivatized by pentafluorobenzylation of the carboxyl group, and trimethylsilylation of the hydroxyl functions. Derivatized s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 5 publications
0
48
0
Order By: Relevance
“…Although a series of sensitive and accurate methods have been described for determination of lovastatin in biological fluids, but all these methods require the use of sophisticated and relatively non-popular instrumentations such as gas chromatography/mass spectrometry [5][6][7] or, more recently, highperformance liquid chromatography/mass spectrometry, 8,9) the availability of a simple, popular and cost-effective method for this purpose remains a limiting factor against pharmacokinetic studies on this drug. The purpose of this investigation was to develop a rapid, popular, and sensitive analytical method, based on HPLC with UV detection of lovastatin in human plasma in order to, primarily, be used throughout a bioequivalence study.…”
Section: 4)mentioning
confidence: 99%
“…Although a series of sensitive and accurate methods have been described for determination of lovastatin in biological fluids, but all these methods require the use of sophisticated and relatively non-popular instrumentations such as gas chromatography/mass spectrometry [5][6][7] or, more recently, highperformance liquid chromatography/mass spectrometry, 8,9) the availability of a simple, popular and cost-effective method for this purpose remains a limiting factor against pharmacokinetic studies on this drug. The purpose of this investigation was to develop a rapid, popular, and sensitive analytical method, based on HPLC with UV detection of lovastatin in human plasma in order to, primarily, be used throughout a bioequivalence study.…”
Section: 4)mentioning
confidence: 99%
“…In the reported gas chromatography-mass spectrometric method (Morris et al 1993), the sensitivity was improved by derivatization, but it is a timeconsuming process. LC-MS/MS methods (Dong et al 2008;Haiyan et al 2008;Lin et al 2008;Nageswararao et al 2012;Ramakrishna et al 2007;Xiao et al 2006;Xiu and Chris 2003;Wu et al 1997) have also been reported with increased sensitivity but the inter-conversion between lovastatin to lovastatin hydroxy acid has not been studied in these methods, which could lead to pseudo estimation of lovastatin in plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous methods for analysis of simvastatin and its metabolites determination in human plasma by HPLC methods with difference detectors (ultraviolet, fluorescence and mass spectrometry) have been published [4][5][6][7][8][9]. In addition, some methods of gas chromatography with mass spectrometry for determination of simvastatin and its metabolites have also been published [10][11]. However, most of these methods are tedious and time consuming, which also considered costly for routine analysis work.…”
Section: Introductionmentioning
confidence: 99%